Consecration rituals in South Asia - Keul, István. (Numen Book Series, 2017)
The essays in the volume Consecration Rituals in South Asia address the ritual procedures that accompany the installation of temple images in Shaiva, Vaishnava, Buddhist and Jain contexts, in various traditions and historical periods. Through the performance of complex rites designated with the term pranapratishtha (establishment of, or infusion with, life), man-made sculptures are ritually transformed into (receptacles of) deities. The collection is thematically and methodically broad, with a large number of detailed textual studies, but also with ethnographic contributions that discuss contemporary instances of consecration rituals. Among the overarching themes are issues related to historical continuity and change, as well as transformational moments in such rituals. Contributors are: Marie-Luce Barazer-Billoret, Marzenna Czerniak-Drożdżowicz, Ronald M. Davidson, Shingo Einoo, Marko Geslani, Dominic Goodall, Ellen Gough, István Keul, Elisabeth Raddock, S.A.S Sarma, Anna A. Ślączka, Annette Wilke.